editing
approved
editing
approved
return ((m*(n-k)+m-1)*EulerianNumber(n-1, k-1, m) + \
(m*k+1)*EulerianNumber(n-1, k, m))
return (add(add(EulerianNumber(n, j, m)*binomial(j, n - k) \
for j in (0..n))/((-m)^k*(k+1)) for k in (0..n)))
proposed
editing
editing
proposed
EulerianNumber[n_, k_, m_] := EulerianNumber[n, k, m] = If[n == 0, If[k == 0, 1 , 0], (m*(n-k) + m - 1)*EulerianNumber[n-1, k-1, m] + (m*k + 1)* EulerianNumber[n-1, k, m]];
BS[n_, m_] := Sum[Sum[EulerianNumber[n, j, m]*Binomial[j, n-k], {j, 0, n}]/ ((-m)^k*(k+1)), {k, 0, n}]
a[n_] := Product[If[Divisible[n+1, p] || Divisible[n, p-1], p, 1], {p, Prime /@ Range @ PrimePi[n+1]}] * BS[n, 2];
Table[a[n], {n, 0, 25}] (* Jean-François Alcover, Jun 27 2019, from Sage *)
approved
editing
proposed
approved
editing
proposed
reviewed
approved
proposed
reviewed
editing
proposed